Differential diagnosis of lipoic acid synthesis defects. Issue 6 (1st September 2016) - Tort, Frederic; Ferrer‐Cortes, Xènia; Ribes, Antonia
Abstract: Lipoic acid (LA) is an essential cofactor required for the activity of five multienzymatic complexes that play a central role in the mitochondrial energy metabolism: four 2‐oxoacid dehydrogenase complexes [pyruvate dehydrogenase (PDH), branched‐chain ketoacid dehydrogenase (BCKDH), 2‐ketoglutarate dehydrogenase (2‐KGDH), and 2‐oxoadipate dehydrogenase (2‐OADH)] and the glycine cleavage system (GCS). LA is synthesized in a complex multistep process that requires appropriate function of the mitochondrial fatty acid synthesis (mtFASII) and the biogenesis of iron–sulphur (Fe‐S) clusters. Defects in the biosynthesis of LA have been reported to be associated with multiple and severe defects of the mitochondrial energy metabolism. In recent years, disease‐causing mutations in genes encoding for proteins involved in LA metabolism have been reported: NFU1, BOLA3, IBA57, LIAS, GLRX5, LIPT1, ISCA2, and LIPT2 . These studies represented important progress in understanding the pathophysiology and molecular bases underlying these disorders. Here we review current knowledge regarding involvement of LA synthesis defects in human diseases with special emphasis on the diagnostic strategies for these disorders. The clinical and biochemical characteristics of patients with LA synthesis defects are discussed and a workup for the differential diagnosis proposed.